Perception of control and detection of fraud in companies in Sucre - Manabí in the period 2020 - Gautherot Hernández, Emilia Melani (2024)
In a globalized world, it is necessary to constantly review what happens within organizations, in order to obtain reliable information on the activities carried out. Over the years, forensic auditing has become one of the most important pillars to be able to detect fraud in companies, with the aim of minimizing/eradicating it and thus achieving adequate internal control. For this reason, the present investigation was carried out in the companies of the Sucre canton of the province of Manabí. The methodology used is descriptive-deductive and consists of documentary analysis and a survey of ninety-three professionals in the area. The main objective of the investigation is to determine the main causes of fraud within organizations with the purpose of dissuading them and eradicating them over time. Finally, it was possible to observe that the absence of personal/professional ethics is the one that affects the commission of fraud, as well as that the internal audit is the one that allows the detection of economic crimes in companies. Thus, financial and forensic auditing are fraud detection and prevention tools inside and outside organizations.